Towards promoting youth mental health in Aotearoa/New Zealand: Holistic "houses" of health - Anae, Melanie; Moewaka Barnes, Helen; McCreanor, Tim; Watson, Peter (Clifford Beers Foundation, 2002)
A study of the literature on mental health promotion suggests that to a far greater extent than ‘physical’ health concerns, mental health seems to be dominated by the illness focus of established clinical perspectives and practices. In Aotearoa/New Zealand this leaves little in the way of conceptual space or fiscal resources for the development of new preventative possibilities of population-oriented measures focussed on enhancing social and physical environments. Outflanking this unfortunate impasse, indigenous Maori and Samoan (Pacific) conceptual frameworks for health offer holistic theoretical foundations upon which we can work for health through positive development. This paper examines these frameworks and the youth development paradigm to draw out parameters of what might count as healthy youth development in this country.
Keywords: Mental health promotion; Youth; Maori; Samoans; Pakeha; New Zealand; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321204 Mental health